Feedback and learning in tennis: Conceptualisation, classification, and practical implications - Fonseca Morales, A.; Martínez-Gallego, R. (Coaching and Sport Science Review, 2022)
This article defines the concept of feedback, proposes a classification of the different types of feedback, and explores the application of extrinsic feedback by tennis coaches. Furthermore, the influence of feedback on the learning and performance of tennis players is analysed. Finally, a series of practical implications that coaches can consider evaluating the feedback they provide to their players and to make the teachinglearning- evaluation process more effective in their training sessions are presented.